EARLY CHILDHOOD EDUCATION PRINCIPALS' STRATEGIES IN IMPLEMENTING TRANSFORMATIONAL LEADERSHIP TO EMPOWER TEACHERS IN AN ERA OF CHANGE - Iwan Perdana; Yuliana Nurhayati (Journal of Innovation Research and Knowledge, 2026)
This study intends to explore the subjective experiences of school principals in implementing transformational leadership to empower Early Childhood Education (PAUD) teachers. A phenomenological approach is utilised to understand the essential meaning of the experience. Data were acquired through in-depth interviews with four PAUD principals and were evaluated thematically. The findings of the study reveal three main themes, namely (1) Leadership as Inspiration and Exemplary in an Empowering Space, (2) Mentoring Strategies through Communication, Mentoring, and Appreciation to Fight Resistance, and (3) Leadership Success through Changing the "Soul" of Teachers and a Living School Climate. This study concludes that the effectiveness of transformational leadership in early childhood education lies in the ability of principals to connect inspirational values with contextual and empathetic mentoring strategies, thereby awakening the professional "soul" of teachers. Implication: leadership development programs should place greater emphasis on building reflective capacity and coaching skills that align with the unique characteristics of early childhood education units.